Characterization of the inter-annual, seasonal, and diurnal variations of condensation particle concentrations at Neumayer, Antarctica - Weller, Rolf; Minikin, A.; Wagenbach, Dietmar; Dreiling, V. (Atmospheric chemistry and physics, 2011)
Abstract. Continuous condensation particle (CP) observations were conducted from 1984 through 2009 at Neumayer Station under stringent contamination control. During this period, the CP concentration (median 258 cm −3) showed no significant long term trend but exhibited a pronounced seasonality characterized by a stepwise increase starting in September and reaching its annual maximum of around 10 3 cm −3 in March. Minimum values below 10 2 cm 3 were observed during June/July. Dedicated time series analyses in the time and frequency domain revealed no significant correlations between inter-annual CP concentration variations and atmospheric circulation indices like Southern Annular Mode (SAM) or Southern Ocean Index (SOI). The impact of the Pinatubo volcanic eruption and strong El Niño events did not affect CP concentrations. From thermodenuder experiments we deduced that the portion of volatile (at 125 °C) and semi-volatile (at 250 °C) particles which could be both associated with biogenic sulfur aerosol, was maximum during austral summer, while during winter non-volatile sea salt particles dominated. During September through April we could frequently observe enhanced concentrations of ultrafine particles within the nucleation mode (between 3 nm and 7 nm particle diameter), preferentially in the afternoon.